2020
DOI: 10.1038/s41598-020-72138-9
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal ‘gene drives’ harness indigenous bacteria for bioremediation

Abstract: Engineering bacteria to clean-up oil spills is rapidly advancing but faces regulatory hurdles and environmental concerns. Here, we develop a new technology to harness indigenous soil microbial communities for bioremediation by flooding local populations with catabolic genes for petroleum hydrocarbon degradation. Overexpressing three enzymes (almA, xylE, p450cam) in Escherichia coli led to degradation of 60–99% of target hydrocarbon substrates. Mating experiments, fluorescence microscopy and TEM revealed indige… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Moreover, microbial plasmids believed to be responsible for the continuous progression, evolution, and distribution of novel biodegradable genes/enzymes (Zhang et al, 2016 ; Jeffries et al, 2019 ). These novel genes/enzymes have endowed microorganism's biodegradation capability to remove or detoxify a wide variety of environmental pollutants due to their inheritance horizontal gene transfer property (Singh V. et al, 2018 ; Jaiswal et al, 2019 ; Li et al, 2019 ; Phale et al, 2019 ; French et al, 2020 ). The microbial remediation process can be further improved via successful application of genome editing and biochemical techniques that modify existing strains and result in the development of a genetically modified organism capable of simultaneously degrading several xenobiotics (Shanker et al, 2011 ; Zhang et al, 2016 ; Hussain et al, 2018 ; Janssen and Stucki, 2020 ).…”
Section: Bioremediation Potential Of Microorganisms For Xenobiotic Comentioning
confidence: 99%
“…Moreover, microbial plasmids believed to be responsible for the continuous progression, evolution, and distribution of novel biodegradable genes/enzymes (Zhang et al, 2016 ; Jeffries et al, 2019 ). These novel genes/enzymes have endowed microorganism's biodegradation capability to remove or detoxify a wide variety of environmental pollutants due to their inheritance horizontal gene transfer property (Singh V. et al, 2018 ; Jaiswal et al, 2019 ; Li et al, 2019 ; Phale et al, 2019 ; French et al, 2020 ). The microbial remediation process can be further improved via successful application of genome editing and biochemical techniques that modify existing strains and result in the development of a genetically modified organism capable of simultaneously degrading several xenobiotics (Shanker et al, 2011 ; Zhang et al, 2016 ; Hussain et al, 2018 ; Janssen and Stucki, 2020 ).…”
Section: Bioremediation Potential Of Microorganisms For Xenobiotic Comentioning
confidence: 99%
“…Nonetheless, some studies have shown that bacterial vectors can be used for the delivery of plasmids to the microbiota found in contaminated soil; this enhances the rate at which plasmidencoded enzymes can digest petroleum hydrocarbons. Once the carbon source is removed, the plasmids disappear, most likely because they no longer provide a selective advantage (French et al, 2020). This represents a promising strategy for removing contaminants with minimal disturbance to the environment.…”
Section: Industrial Applicationsmentioning
confidence: 99%
“…Although they are efficient, there are some factors such as the ecological characteristics that can influence the degradation process outcome. Additionally, bioremediation studies presented the potential for and capability of microorganism biodegradability when having to deal with a large number of environmental contaminants, all because of the mutagenesis processes [113][114][115][116]. In Figure 12, the chemical structures of various xenobiotic compounds are presented.…”
Section: Basics Of Xenobiotic Compoundsmentioning
confidence: 99%